Conscientious objection and physician-assisted suicide: a viable option in the UK?. Issue 4 (15th November 2018) - Willis, Derek; George, Rob
Abstract : Conscience objection is a proposed way of ensuring that medical practitioners who object to physician-assisted suicide may avoid having to be involved in such a procedure if this is legalised. This right on the part of healthcare professionals already exists in certain circumstances. This paper examines the ethical and legal grounds for conscientious objection for medical professionals and shows how it is heavily criticised in circumstances where it is already used. The paper comes to the conclusion that as the grounds and application of conscience objection are no longer as widely accepted, its future application in any legislation can be called into question.